Novel metallic titanium fluoride: A promising high capacity and superionic conductivity anode in Li-, Na-, and K-ion batteries. (April 2023) - Zhou, Min; Shen, Yanqing; Liu, JiaJia; Lv, LingLing; Zhang, Yu; Meng, Xianghui; Yang, Xin; Zheng, Yangdong; Zhou, Zhongxiang
Abstract: The transition metal fluorides have huge advantage as anode due to the small atomic mass of the F atom. But the formation of Li–F rings reduced the cycle life, and the open-framework structure induced the high diffusion barriers. We designed a non-open framework 1T-TiF2 structure. The remaining 3d electrons of Ti induced the 1T-TiF2 structure has good electronic conductivity, and large formation energy of 1T-TiF2 structure block the formation of Li–F rings. The 1T-TiF2 structure could serve as anode in Li-ion, Na-ion, and K-ion batteries with high stiffness, superionic conductivity and long cycle life. Our calculate results indicated that the 1T-TiF2 anode has competitive theoretical capacitance (208.08 mA h g −1 for Li-ion battery, 277.45 mA h g −1 for Na-ion battery, and 208.08 mA h g −1 for K-ion battery). Furthermore, the good thermal, dynamic stability, oxidative corrosion resistance, and hydrophilicity confirmed the possibility of preparing 1T-TiF2 structure under laboratory conditions. Our study provides a reference for the light weighting of anodes. Highlights: For the first time, the novel metallic non-open framework 2D TiF2 is predicted. High stiffness avoided the deformation of TiF2 and the formation of Li–F rings. TiF2 anode has excellent electric/ionic conductivity and large capacitance.